2021
DOI: 10.1101/2021.08.19.456809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized detection of allelic imbalances specific for homologous recombination deficiency improves the prediction of clinical outcomes in cancer

Abstract: Specific patterns of genomic allelic imbalances (AIs) have been associated with Homologous recombination DNA-repair deficiency (HRD). We performed a systematic pan-cancer characterization of AIs across tumor types, revealing unique patterns in ovarian cancer. Using machine learning on a multi-omics dataset, we generated an optimized algorithm to detect HRD in ovarian cancer (ovaHRDscar). ovaHRDscar improved the prediction of clinical outcomes in three independent validation cohorts (PCAWG, HERCULES, TERVA). Ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…All the tumor samples used in this study were subjected to the genomic ovaHRDscar test to evaluate homologs recombination (HR) status (Table. S, 3) (26). We treated the treatment naive HRD or HRP tumor derived PDCs (n=3 each) with olaparib and evaluated the treatment responses as a decrease in the abundance of CK7+ tumor cells compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…All the tumor samples used in this study were subjected to the genomic ovaHRDscar test to evaluate homologs recombination (HR) status (Table. S, 3) (26). We treated the treatment naive HRD or HRP tumor derived PDCs (n=3 each) with olaparib and evaluated the treatment responses as a decrease in the abundance of CK7+ tumor cells compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…To define an experimental signature of BRCAness, we compared the expression profiles of control (i.e HRD, or BRCAness+) and BRCA1 -restored (i.e HRP, or BRCAness-) cells. In contrast, the clinical BRCAness signature was defined as the deconvoluted 28 gene expression changes from The Cancer Genome Atlas (TCGA) cohort 29 where HGSOC patients were stratified into BRCAness +/-groups based on a genomic classifier called ovaHRDscar 30 . Kaplan-Meier survival analysis confirmed that both transcriptional BRCAness signatures were associated with improved overall survival (OS) in ovarian serous cystadenocarcinoma patients in TCGA cohort ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For most of the patients sampled at Turku University Hospital, we had, in addition to the fHR score, information available from at least one of the following genomics-based HRD estimates: mutational signature SBS3, mutational signature ID6 (Alexandrov et al, 2013) and/or ovaHRDScar (Perez-Villatoro et al, 2021). For 46% of the patients (n=34), at least one of the available methods for HRD determination disagreed with the other estimates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HR deficiency causes characteristic loss-of-heterozygosity (LOH), large scale transitions (LSTs) and telomeric allelic imbalances (TAI) that can be quantified and used to identify HRD tumors (Takaya et al, 2020; Telli et al, 2016). A recently optimized algorithm (called ovaHRDScar), to quantify these allelic imbalances in HGSC samples, was used for the classification of the samples as HRD or HRP (Perez-Villatoro et al, 2021). A cut-off value of >54 for the sum of LOH, LSTs and TAI was used for classifying a sample as HRD.…”
Section: Methodsmentioning
confidence: 99%